2003
DOI: 10.1149/1.1576222
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube/RuO[sub 2] Nanocomposite Electrodes for Supercapacitors

Abstract: Electrochemical characteristics of electrodes for supercapacitors built from RuO 2 /multiwalled carbon nanotube ͑CNT͒ nanocomposites have been investigated. Capacitances have been estimated by cyclic voltammetry at different scan rates from 5-50 mV/s. Electrostatic charge storage as well as pseudofaradaic reactions of RuO 2 nanoparticles have been affected by the surface functionality of CNTs due to the increased hydrophilicity. Such hydrophilicity enables easy access of the solvated ions to the electrode/elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 19 publications
0
132
1
1
Order By: Relevance
“…Park et al 21 reported on the preparation of RuO 2 nanoparticles dispersed in CNTs along with their performance as active materials in electrochemical capacitors. Ko and Kim 3 prepared chemically activated multi-walled CNTs (A-CNTs) using KOH, and used it as an additive in the fabrication of MnO 2 electrodes to enhance the performance of MnO 2 -based SCs.…”
Section: -11mentioning
confidence: 99%
“…Park et al 21 reported on the preparation of RuO 2 nanoparticles dispersed in CNTs along with their performance as active materials in electrochemical capacitors. Ko and Kim 3 prepared chemically activated multi-walled CNTs (A-CNTs) using KOH, and used it as an additive in the fabrication of MnO 2 electrodes to enhance the performance of MnO 2 -based SCs.…”
Section: -11mentioning
confidence: 99%
“…32,33 The values of specific capacitance reported for manganese oxide in the literature range between 150 and 250 F/g. [16][17][18][19][20][21][22][23][24][25]34 These values are far from the theoretical value, ca.…”
mentioning
confidence: 99%
“…Consequently, the metal oxide coatings on acidtreated CNTs were often nonuniform, although they provided better interaction in comparison with pristine CNTs. Despite these drawbacks, most researchers have used such acid-treated CNTs for various metal oxide coatings, including SnO 2 [160,161,[163][164][165], TiO 2 [159,[166][167][168], RuO 2 [169,170], CeO 2 [162], NiO [171], and mixed oxides [172].…”
Section: Covalentmentioning
confidence: 99%
“…Among these transition metal oxides, ruthenium oxides are regarded as the most promising electrode material for supercapacitor applications due to their high specific capacitance, highly reversible redox reactions, wide potential window, and very long cycle life [192]. Park et al reported a specific capacitance for CNT/RuO 2 (13 wt %) of 450 F/g at a potential scan rate of 20 mV s -1 , which could be further enhanced, by using hydrous ruthenium oxide and functionalized CNTs, to 800 F/g [170]. Reducing the thickness of the RuO 2 layer to 3 nm led to an even higher capacitance (1170F/g at a potential scan rate of 10 mV s -1 ) [149].…”
Section: Supercapacitors and Batteriesmentioning
confidence: 99%